2018
DOI: 10.31219/osf.io/dswge
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Critical Features for Face Recognition

Abstract: Face recognition is a computationally challenging task that humans perform effortlessly. Nonetheless, this remarkable ability is limited to familiar faces and does not generalize to unfamiliar faces. To account for humans’ superior ability to recognize familiar faces, current theories suggest that familiar and unfamiliar faces have different perceptual representations. In the current study, we applied a reverse engineering approach to reveal which facial features are critical for familiar face recognition. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…The current findings showed that the composite face effect with familiar and unfamiliar faces has been manifested at the same ex-Gaussian component—the τ component. This common pattern increases support in the hypothesis that familiar and unfamiliar faces are governed by the same mechanisms (Abudarham et al, 2019). However, this conclusion should be constrained by the possibility that different mechanisms can still produce similar influence on the τ component.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The current findings showed that the composite face effect with familiar and unfamiliar faces has been manifested at the same ex-Gaussian component—the τ component. This common pattern increases support in the hypothesis that familiar and unfamiliar faces are governed by the same mechanisms (Abudarham et al, 2019). However, this conclusion should be constrained by the possibility that different mechanisms can still produce similar influence on the τ component.…”
Section: Discussionsupporting
confidence: 62%
“…This also strengthens the position that familiar and unfamiliar composites are governed by similar (holistic?) processes/constructs (Abudarham et al, 2019). Moreover, since the τ component is associated with attention and working memory processes (Schmiedek et al, 2007) and/or object-based attention processes (Spieler et al, 2001), the current findings support attentional and object-based accounts of the composite face effect (Fitousi, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we propose that the view-invariant perceptual representation is generated for all faces regardless of their familiarity. This suggestion is based on our recent findings that show that the same view-invariant critical features are used for both familiar and unfamiliar faces (Abudarham et al, 2019). We therefore propose that the significant gap in performance between familiar and unfamiliar faces is mediated by the conceptual representation of the familiar face, which may correspond to Bruce and Young's face recognition unit (FRU), which unlike the structural code, is not purely perceptual, but links the perceptual and the conceptual knowledge about the familiar person.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore named them critical features, as they are critical for the identity of a face. In contrast, changing another set of facial features did not change the identity of the face, and we therefore named them non-critical features (Abudarham, Shkiller, & Yovel, 2019;Abudarham & Yovel, 2016 (Figure 3A and Figure S1 and S2). In the learning phase, we presented pairs of images of the same identity that differed in critical features or in non-critical features.…”
Section: Studymentioning
confidence: 99%